Pengaruh Product Quality, Harga Dan Brand Ambassador Terhadap Keputusan Pembelian Sepatu Specs Di Kota Malang - Akbar, Risqi Hi’mal; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze the impact of product quality, price and brand ambassador on purchasing decisions for specs shoes in Malang City. Using multiple linear regression methods, this research focuses on explanatory research with a quantitative approach. A research sample of 100 consumers was taken using the Malhotra formula. Data analysis was carried out with the help of SPSS version 25 software, including validity test, reliability test, normality test, classical assumption test, hypothesis test, and R2 coefficient of determination test. The research results show that overall, product quality, price and brand ambassador have a significant influence on consumer purchasing decisions for spec shoe products in Malang City. Specifically, price has a positive impact on purchasing decisions, while product quality and brand ambassador do not have a significant influence on consumer purchasing decisions. Keywords: Product Quality, Harga, Brand Ambassador, Purchasing Decisions